2019
DOI: 10.1021/acsnano.9b00154
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Organometal–Halide Perovskite Lasers for Speckle Reduction in Imaging Projection

Abstract: Disorder is emerging as a strategy for fabricating random laser sources with very promising materials, such as perovskites, for which standard laser cavities are not effective or too expensive. We need, however, different fabrication protocols and technologies for reducing the laser threshold and controlling its emission. Here, we demonstrate an effectively solvent-engineered method for high-quality perovskite thin films on a flexible polyimide substrate. The fractal perovskite thin films exhibit excellent opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 36 publications
(55 reference statements)
4
61
0
Order By: Relevance
“…Due to the roughness of the MAPB layer, random lasing action is observed from the MAPB/PMMA sample. Such random lasing from perovskite polycrystalline thin films have already been demonstrated in the literature in MAPB thin layers [43,45]. The PL spectroscopy demonstrating the random lasing is shown in the section 2 of the supplementary.…”
supporting
confidence: 62%
See 1 more Smart Citation
“…Due to the roughness of the MAPB layer, random lasing action is observed from the MAPB/PMMA sample. Such random lasing from perovskite polycrystalline thin films have already been demonstrated in the literature in MAPB thin layers [43,45]. The PL spectroscopy demonstrating the random lasing is shown in the section 2 of the supplementary.…”
supporting
confidence: 62%
“…directly from polycrystalline and nanocrystals thin films. This has indeed been demonstrated in iodine-based perovskites [27][28][29][30][31], chloride-based perovskites [32] and bromide-based perovskites [32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
mentioning
confidence: 68%
“…Finally, the natural properties that halide perovskite can be advanced to exible lasing devices will denitely broaden the material's prospects. 35,36 Convenient fabrication and natural large grains make MAPbBr 3 thin lms more accessible, affordable, and operable for further uses as in-plane light source.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the use of disordered gain materials has emerged as a strategy for fabricating random laser sources. Recently, Wang et al demonstrated a random laser in curved perovskite MAPbBr 3 thin films on flexible substrates by using the solvent-engineered method ( Figure 6E) [75]. Under 355 nm excitation with 0.5 ns and 1 kHz, the lasing threshold was 2.5 mJ/cm 2 with emission FWHM of ~1.8 nm, which can be further reduced by increasing the local curvature of the film arising from the variation of the scattering strengths of the bent thin film.…”
Section: Perovskite Random Lasermentioning
confidence: 99%